Women’s Organizations and the Movement for Gender Equality and the Abolition of the Head-of-family System in South Korea - Dabphet, Siriporn (ASIA PARIDARSANA, 2021)
The paper examines the development of, and the factors impacting on, the women’s organizations and the movement in South Korea for gender equality through the process of law revision, which contributed to the revision of the Family Law and the abolition of the head-of-family system in 2005. The paper also examines the current situation of women’s rights in South Korea. A historical qualitative research methodology was used through a study of documents. The study has found that the 1912 head-of-family system, which placed the man as the legal head of the family, had become the symbol of gender inequality in Korean society. Women’s organizations have played a major role since the 1950s in the movement for gender equality and revision of the Family Law. The essence of the women’s organization movement in South Korea lies in a struggle for gender equality, focusing on the abolition of the head-of-family system as the symbol of gender inequality. The movement has also involved campaigns for equal opportunities for and treatment of men and women in employment and the elimination of sexual harassment and violence against women. The landmark reform of the Family Law will be analyzed in connection with the local women’s movement, national politics, and international organizations. The 1990s saw the role of the women’s organizations in the human rights movements following the global trend. The women’s organizations had an influence on the legislative process and the implementation of women’s policies of the state. The head-of-family system was finally abolished in 2005. However, the movement to abolish discrimination against women, which has given rise to gender-based conflict and controversy in South Korean society nowadays, is also under way.